2022
DOI: 10.1002/ptr.7381
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sesame, canola, and sesame‐canola oils on cardiometabolic risk factors in overweight adults: a three‐way randomized triple‐blind crossover clinical trial

Abstract: Limited data exist on the cardiometabolic effects of sesame oil compared with canola oil. In the present study, 77 overweight adults were randomized to replace their regularly consumed oils with canola (CO), sesame (SO), and sesame‐canola oils (SCO, 40% SO, and 60% CO) in three 9‐week phases. Blood pressure, visceral adiposity index, serum apo‐proteins (APOs) and lipid profile, glycemic control markers, kidney markers, liver enzymes, and cardiovascular disease risk scores were assessed at baseline and endline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In contrary, a very recent study by Moghtaderi et al . [ 163 ] did not prove positive effect of sesame oil on BP; however, in this study the exact amount of consumed oil in patients’ food was not specified, only the time of consumption (9 weeks). Positive effect of sesame oil (or sesamin) consumption on hypertension and endothelial function was confirmed in a clinical study of Karatzi et al .…”
Section: The Effect Of Sesame Oil On Cardiovascular Health and Diseasesmentioning
confidence: 82%
“…In contrary, a very recent study by Moghtaderi et al . [ 163 ] did not prove positive effect of sesame oil on BP; however, in this study the exact amount of consumed oil in patients’ food was not specified, only the time of consumption (9 weeks). Positive effect of sesame oil (or sesamin) consumption on hypertension and endothelial function was confirmed in a clinical study of Karatzi et al .…”
Section: The Effect Of Sesame Oil On Cardiovascular Health and Diseasesmentioning
confidence: 82%
“…In healthy subjects, no consistent effects on blood glucose levels, lipid profiles, and anthropometric measures were observed among participants provided sesame seed, oil, flour, or sesamin 47,48,60,61,63,85 . Similar inconsistencies in these outcomes were observed for hypercholesterolemic/hyperlipidemic, overweight, and hypertensive subjects 66–68,70–72,88–90 . Furthermore, in hypertensive individuals, overall effects on blood pressure were inconsistent.…”
Section: Methodsmentioning
confidence: 91%
“…Given the existence of evidence about the effectiveness of sesame in glucose metabolism, some RCTs similar to our overall pooled results found that sesame may improve glycemic indices (Aslam et al, 2019; Ghoreishi et al, 2022; Mohammad Shahi et al, 2017). While, others proposed that sesame could not be a useful adjuvant therapy in controlling glycemic parameters (Bahadoran et al, 2015; Moghtaderi et al, 2022). The variability of results in these studies may be attributed to the differences in study design, individual characteristics, sesame dose, and intervention duration.…”
Section: Discussionmentioning
confidence: 99%
“…While, others proposed that sesame could not be a useful adjuvant therapy in controlling glycemic parameters (Bahadoran et al, 2015;Moghtaderi et al, 2022). The variability of results in these studies may be attributed to the differences in study design, individual characteristics, sesame dose, and intervention duration.…”
Section: Discussionmentioning
confidence: 99%